2007
DOI: 10.1111/j.1467-9566.2007.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of patient and doctor gender on diagnosing coronary heart disease

Abstract: Using novel methods, this paper explores sources of uncertainty and gender bias in primary care doctors' diagnostic decision-making about coronary heart disease (CHD). Claims about gendered consultation styles and quality of care are re-examined, along with the adequacy of CHD models for women. Randomly selected doctors in the UK and the US (n = 112, 56 per country, stratified by gender) were shown standardised videotaped vignettes of actors portraying patients with CHD. Patients' age, gender, ethnicity and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 43 publications
(75 reference statements)
1
38
1
1
Order By: Relevance
“…Well-known variations in illness rates by gender are therefore not only a consequence of differences in the biological or behavioral risk structure, but might also be socially constructed (Hor-ton, 2007). In a qualitative work, Adams et al (2007) explored sources of gender bias in the decision making process of primary care doctors in the United Kingdom and United States. During the interviews that were part of the present study, doctors were asked to explain and justify diagnostic and therapeutic decisions for a CHD patient.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known variations in illness rates by gender are therefore not only a consequence of differences in the biological or behavioral risk structure, but might also be socially constructed (Hor-ton, 2007). In a qualitative work, Adams et al (2007) explored sources of gender bias in the decision making process of primary care doctors in the United Kingdom and United States. During the interviews that were part of the present study, doctors were asked to explain and justify diagnostic and therapeutic decisions for a CHD patient.…”
Section: Discussionmentioning
confidence: 99%
“…Because such models of somatisation (Martin & Lemos, 2002) and more specifically, pain behaviours conveying distress, are more intimately associated with the female stereotype (e.g. Adams et al, 2008;McCaffery & Ferrell, 1992), we have reasons to expect that the influence of the latter on pain judgements depends on the patient's sex.…”
Section: Psychology and Health 1645mentioning
confidence: 99%
“…Coronary heart disease is still considered a male disease. In a recent study in primary care conducted in the UK, the view was supported that knowledge about female heart disease is not yet fully integrated into 'received medical wisdom' (Adams et al 2007). In their study, physicians were shown standardized videotaped vignettes and physicians took account of patients' age when diagnosing CHD symptoms in men but not in women.…”
Section: Male Biasmentioning
confidence: 99%
“…Women however present more often than men with atypical symptoms, which means that those findings may underestimate gender bias in CHD diagnosis. In Adams et al (2007) video-vignette study, doctors were more likely to look for psychological cues and search for psychological explanations for key CHD symptoms in women than for symptoms in men. Possibly, when presenting atypical symptoms, women may be even more disadvantaged.…”
Section: Gender-role Ideologymentioning
confidence: 99%